ISU LGBT DI MALAYSIA : SATU TINJAUAN TERHADAP ASPEK KAJIAN: LGBT ISSUES IN MALAYSIA: A REVIEW OF RESEARCH ASPECTS (International Seminar on Syariah and Law (INSLA), 2020)
The word "LGBT" is becoming the most popular issue talked about among Malaysians regardless of age, race, religion, and culture. This is due to various issues that have arisen brought by this group in society. The LGBT group that hides behind the propaganda of freedom and human rights has made it a focal point for various studies at various levels. This paper is intended to review the extent to which studies that touch on LGBT issues have been implemented in Malaysia. Next, conclude and suggesting other studies that are seen as potential for implementation. Writing will use qualitative methods concerning library studies that include various forms of material such as journal articles, newspapers, fatwas, scientific studies, and others. The findings of writing found that several aspects being the focus of previous researchers, namely aspects of development, acceptance, and punishment, effects and issues that arise, factors involved, as well as suggestions to overcome LGBT symptoms. Thus, several other aspects of the study have been submitted as suggestions for further studies related to LGBT issues in Malaysia that can be implemented. The word "LGBT" is becoming the most popular issue talked about among Malaysians regardless of age, race, religion, and culture. This is due to various issues that have arisen brought by this group in society. The LGBT group that hides behind the propaganda of freedom and human rights has made it a focal point for various studies at various levels. This paper is intended to review the extent to which studies that touch on LGBT issues have been implemented in Malaysia. Next, conclude and suggesting other studies that are seen as potential for implementation. Writing will use qualitative methods concerning library studies that include various forms of material such as journal articles, newspapers, fatwas, scientific studies, and others. The findings of writing found that several aspects being the focus of previous researchers, namely aspects of development, acceptance, and punishment, effects and issues that arise, factors involved, as well as suggestions to overcome LGBT symptoms. Thus, several other aspects of the study have been submitted as suggestions for further studies related to LGBT issues in Malaysia that can be implemented. Perkataan “LGBT” semakin menjadi bualan dalam kalangan rakyat Malaysia tanpa mengira pelbagai peringkat umur, kaum, agama dan budaya. Perkara ini berlaku ekoran daripada pelbagai isu yang timbul yang dibawa oleh kelompok ini dalam masyarakat. Kelompok LGBTyang berselindung disebalik propaganda kebebasan dan hak asasi manusia ini telah menjadikan ia sebagai suatu tumpuan terhadap berbagai kajian dipelbagai peringkat. Penulisan ini adalah bertujuan untuk meninjau sejauhmanakah kajian yang menyentuh tentang isu LGBT telah dilaksanakan di Malaysia. Seterusnya membuat rumusan dan mencadangkan kajian-kajian lain yang dilihat berpotensi untuk dilaksanakan. Penulisan akan menggunapakai kaedah kualitatif dengan merujuk kepada kajian kepustakaan yang merangkumi pelbagai bentuk bahan seperti artikel jurnal, akhbar, fatwa, kajian-kajian ilmiah, dan pelbagai lagi. Hasil penulisanmendapati bahawa terdapat beberapa aspek yang kajian menjadi tumpuan pengkaji sebelum ini iaitu aspek perkembangan, penerimaan dan hukuman, kesan dan isu yang timbul, faktor-faktor penglibatan, serta cadangan bagi mengatasi gejala LGBT. Justeru, beberapa cadangan aspek kajian yang lain telah dikemukakan sebagai cadangan kajian-kajian lanjutan yang berkait dengan isu LGBT di Malaysia yang boleh dilaksanakan.